2014
DOI: 10.1371/journal.pone.0087243
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Platelet-Derived Microparticles Is Related to Painful Vaso-Occlusive Phenotype Severity in Sickle Cell Anemia

Abstract: High plasma level of microparticles (MPs) deriving mainly from erythrocytes and platelets has been detected in sickle cell anemia (SCA) patients. Flow cytometry was used to determine the concentration of MPs in two groups of SCA patients exhibiting marked differences in painful vaso-occlusive crisis rates [a non-severe group (n = 17) and a severe group (n = 12)], and in a control group composed of healthy subjects (n = 20). A 3- to 4-fold increase of total MP plasma concentration was detected in SCA patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 24 publications
(40 reference statements)
2
44
1
Order By: Relevance
“…MPs were isolated from plasma by ultracentrifugation as previously described, within 2 h of blood collection, and were stored at −80°C until used (Nieuwland et al , ; Nebor et al , ). MP analysis by flow cytometry was performed using a FC500 flow cytometer (Beckman Coulter, CA, USA) (Nebor et al , , ). The concentration of haem associated with MPs was also quantified using the Quantichrome Haem Assay Kit (Bioassay Systems, Paris, France), after resuspension of MPs in the same volume of buffer (10 mmol/l HEPES pH 7·4, 136 mmol/l NaCl, 5 mmol/l KCl, 2 mmol/l MgCl 2 ) as the plasma volume from which they had been isolated.…”
Section: Methodsmentioning
confidence: 99%
“…MPs were isolated from plasma by ultracentrifugation as previously described, within 2 h of blood collection, and were stored at −80°C until used (Nieuwland et al , ; Nebor et al , ). MP analysis by flow cytometry was performed using a FC500 flow cytometer (Beckman Coulter, CA, USA) (Nebor et al , , ). The concentration of haem associated with MPs was also quantified using the Quantichrome Haem Assay Kit (Bioassay Systems, Paris, France), after resuspension of MPs in the same volume of buffer (10 mmol/l HEPES pH 7·4, 136 mmol/l NaCl, 5 mmol/l KCl, 2 mmol/l MgCl 2 ) as the plasma volume from which they had been isolated.…”
Section: Methodsmentioning
confidence: 99%
“…There are inconsistent data regarding further increases of the concentration of total microparticles during acute painful episodes (38,88)(86,87). A history of at least 3 painful episodes in the previous year was associated with a higher “steady state” plasma concentration of monocyte-derived microparticles in a group of adults with HbSS and HbSβ-thalassemia (91), while another study of adult HbSS patients reported associations of painful episodes in the previous 2 years with lower concentrations of erythrocyte-derived microparticles, but higher total and platelet-derived microparticles (92). …”
Section: Hemostatic Alterations Of Scdmentioning
confidence: 99%
“…Indeed, it has been shown that MPs originated from sickle RBCs may trigger coagulation, increase the production the production of radical oxygen species by endothelial cells, induce erythrocyte adhesion to endothelial cells and endothelial cell apopotosis, as well as, trigger renal vaso-occlusive crisis in a sickle mouse model [2426]. Furthermore, several studies also supported a role of MPs in the occurrence of several complications in patients with SCA [15,2728]. While these data strongly suggest that MPs are not only bio-markers but also bio-effectors in SCA, no study looked at the presence and/or at the circulating MP profile in HbSC patients.…”
Section: Introductionmentioning
confidence: 99%